A Case Control in A Sub-Urban Area: Maternal Height and Nutritional Status with the Incidence of Stunting Among Toddlers - Dainy, Nunung Cipta; Kusumaningati, Walliyana; Ashari, Chica Riska; Kushargina, Rosyanne (Universitas Airlangga, 2024)
Indonesia is a country with a high incidence of stunting. In 2022, the prevalence of stunting in Bogor Regency was 24.9%, which was higher than the national average. The Padasuka subdistrict is recognized as a stunting locus area. Children's health is closely linked to the parenting style employed by their parents, particularly mothers. Therefore, this study aims to analyze the maternal factors contributing to the prevalence of stunting among toddlers. This study used an observational approach with a case-control design, conducted from December 2022 to August 2023 in Padasuka, Bogor Regency. Data collection encompassed anthropometric measurements, including the weight and height of toddlers and mothers, maternal characteristics such as age, education, and occupation, and nutritional status. The data were collected using questionnaires and interviews. The research sample consisted of 41 mothers of stunted toddlers (cases) and 41 mothers of normally developing toddlers (controls), resulting in a total of 82 participants. Bivariate analysis to explore the relationships between variables, as well as the chi-squared test and independent t-test to measure the differences in average height and nutritional status. The results of the analysis revealed that maternal height (p=0.000) and nutritional status (p=0.035) were significantly correlated with the incidence of stunting. In addition, there were notable differences in the average values of maternal height and nutritional status between the stunted group and the normally developing group with p-values of 0.038 and 0.040, respectively. Therefore, it can be concluded that maternal height and nutritional status contribute to the incidence of stunting among toddlers.